Digital Accounting Systems, Big Data Analytics, and Ethical Awareness in Improving Public Sector Financial Reporting Quality - Salehoddin, Salehoddin (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to examine the integrated structural relationships among Digital Accounting Systems, Big Data Analytics Capability, and Ethical Awareness in enhancing Public Sector Financial Reporting Quality, with the mediating interplay of Professional Skepticism, Forensic Accounting Practices, and Public Value under AI-driven audit governance. A quantitative approach was employed involving 250 internal auditors/inspectors (regional inspectorates) across East Java Province as the research sample. Data were analyzed using WarpPLS with a Structural Equation Modeling (SEM-PLS) technique. The findings reveal that Digital Accounting Systems, Big Data Analytics Capability, and Ethical Awareness each have a positive and significant effect on Professional Skepticism, Forensic Accounting Practices, and Public Value. Furthermore, Professional Skepticism, Forensic Accounting Practices, and Public Value are proven to positively and significantly contribute to improving Public Sector Financial Reporting Quality. Mediation results also indicate that Professional Skepticism, Forensic Accounting Practices, and Public Value function as important mediating mechanisms in strengthening the influence of Digital Accounting Systems, Big Data Analytics Capability, and Ethical Awareness on financial reporting quality. This research contributes to public sector accounting literature by highlighting the strategic role of digital transformation, analytical capability, and ethical commitment in fostering trustworthy and value-driven government financial accountability. Practically, the findings provide insights for policymakers and internal audit institutions to optimize AI-driven audit governance and reinforce public trust through higher quality financial reporting.